2023
DOI: 10.1002/ajh.26824
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell donor vaccination with cytomegalovirus triplex augments frequencies of functional and durable cytomegalovirus‐specific T cells in the recipient: A novel strategy to limit antiviral prophylaxis

Abstract: To enhance protective cytomegalovirus (CMV)‐specific T cells in immunosuppressed recipients of an allogeneic hematopoietic cell transplant (HCT), we evaluated post‐HCT impact of vaccinating healthy HCT donors with Triplex. Triplex is a viral vectored recombinant vaccine expressing three immunodominant CMV antigens. The vector is modified vaccinia Ankara (MVA), an attenuated, non‐replicating poxvirus derived from the vaccinia virus strain Ankara. It demonstrated tolerability and immunogenicity in healthy adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The outcome measures generally target T-cell responses, and CMV-specific T-cell antigens are usually included in a viral vector vaccine [84]. Recently, in phase I clinical trials, one of these vaccines (CMV-MVA triplex vaccine of the City of Hope Medical Center) have not only demonstrated a safe profile among HSCT participants treated with the vaccine, but also the ability to elicit robust cytotoxic T lymphocyte (CTL) responses through donor vaccination in CMV-positive recipients [85,101]. Indeed, CMV-specific CD137 + CD8 + T cells were significantly higher (p-value < 0.0001 and p-value = 0.0174, respectively) in recipients who received an HCT from a Triplex-vaccinated matched related donor than an unvaccinated donor (control cohort) [101].…”
Section: Viral Vectored Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…The outcome measures generally target T-cell responses, and CMV-specific T-cell antigens are usually included in a viral vector vaccine [84]. Recently, in phase I clinical trials, one of these vaccines (CMV-MVA triplex vaccine of the City of Hope Medical Center) have not only demonstrated a safe profile among HSCT participants treated with the vaccine, but also the ability to elicit robust cytotoxic T lymphocyte (CTL) responses through donor vaccination in CMV-positive recipients [85,101]. Indeed, CMV-specific CD137 + CD8 + T cells were significantly higher (p-value < 0.0001 and p-value = 0.0174, respectively) in recipients who received an HCT from a Triplex-vaccinated matched related donor than an unvaccinated donor (control cohort) [101].…”
Section: Viral Vectored Vaccinementioning
confidence: 99%
“…Recently, in phase I clinical trials, one of these vaccines (CMV-MVA triplex vaccine of the City of Hope Medical Center) have not only demonstrated a safe profile among HSCT participants treated with the vaccine, but also the ability to elicit robust cytotoxic T lymphocyte (CTL) responses through donor vaccination in CMV-positive recipients [85,101]. Indeed, CMV-specific CD137 + CD8 + T cells were significantly higher (p-value < 0.0001 and p-value = 0.0174, respectively) in recipients who received an HCT from a Triplex-vaccinated matched related donor than an unvaccinated donor (control cohort) [101]. The promising results of the cellular and humoral responses obtained in phase I have enabled some of these vaccines to enter phase II clinical trials [85,92].…”
Section: Viral Vectored Vaccinementioning
confidence: 99%
“…However, it is likely that the majority of allo-HCT recipients were transplanted with a non-naïve donor graft, given that these transplants took place at a time when vaccination rates in the US and Europe reached up to 78% [ 36 ]. Multiple studies have shown that donor natural or vaccine-induced immunity can be transferred to the recipient and boosted via vaccination [ 37 , 38 , 39 ]. How COH04S1 compares to Comirnaty ® in stimulating SARS-CoV-2-specific immunity in this heavily treated, likely non-naïve population is being evaluated in the randomized blinded portion of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, signi cant progresses have been made in understanding the immune control system during CMV exposure following allo-HSCT (22)(23)(24)(25). Earlier studies suggested that the reconstitution of CD4 + T cells precedes and subsequently orchestrates CD8 + T cell reconstitution to provide enhanced protection against CMV disease(26, 27).…”
Section: Discussionmentioning
confidence: 99%